Manual of industrial project analysis in developing countries : annex to volume 1- industrial profiles - Organisation for Economic Co-operation and Development (Paris : Development Centre of the Organisation for Economic Co-operation and Development, 1968)
This is an appendix to the Volume 1 of OECD's Manual on Industrial Project Analysis. It includes a series of profiles for goods that are frequently considered for production in developing countries.
Includes bibliographical references.
lje 03/10/2018
Loans
Keywords: Industries; Economic development projects; Project management